El discurso patriarcal en La Ruta de su Evasión de Yolanda Oreamuno: una lectura de la otredad a través de la polifonía Bajtiniana - Zapparoli Zecca, Mayra (2007)
We propose to make a reading of La ruta de su evasión using some Bajtin’s conception. Confronting masculine and feminine voices from the text. Also to incorporate the gender category for a re-reading because it is one of the principal success of the present feminist critic.